Synthesis, characterization and antibacterial studies of calcite-zincite nanoparticles. (2021) - Sampath Kumar, L.; Shantha, V.; Naik, Chandrashekhar; Rajendra Singh, C.; Hariharan, P.
Abstract: The nanoparticles (Nps) have huge applications in various fields like electronics, environment, cosmetics, material science and biomedical systems, etc. Among the various types of nanoparticles available zinc oxide (zincite/ZnO) and calcium carbonate (calcite/CaCO3 ) are commonly used nanoparticles in biomedical applications. These nanoparticles have advantages with respect to biocompatibility, antimicrobial and antifungal activities, etc. This paper presents, the synthesis of calcite/zincite nanoparticles by Sol-Gel Auto Combustion (SGC) method using precursor as sodium hydroxide and glycine as fuel. The shapes and size of calcite/zincite nanoparticles were characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope ( SEM) and Energy-dispersive X-ray spectroscopy (EDX). The average size of the nanoparticles were found to be 38 nm. It was found that the calcite/zincite nanoparticles exhibited promising antibacterial activity against Escherichia Coli, Enterococcus Faecalis and Staphylococcus Aureus in 24 h and 48 h of incubation by decreasing the viability of the tested bacteria's.